The Effect of Principal’s Leadership and Teacher’s Professionalism on Teacher’s Performance - Setiawan, Beny; Lian, Bukman; Ahyani, Nur (Graduate Program Magister Manajemen Pendidikan, 2022)
Improving teacher’s performance can be done by maximizing teacher professional competence because teacher professional competence is the basis for a teacher in carrying out learning activities and especially in enhancing the role as an educator. The method used in this research is to use quantitative methods with a survey approach. The population is 407 teachers who are in East Baturaja sub-district. Because the population is 100, the sample is taken as a whole and is called the population sample, but if the population is more than 100 then 35% is taken, namely 147 teachers who are sampled by using purposive sampling and to analyze the data researchers use SPSS For Windows Version 21. The results of the study are each point of the problem formulation states that there is a positive and significant influence both partially and simultaneously on principal’s leadership and teacher’s professionalism on teacher’s performance